2013
DOI: 10.1371/journal.pone.0077710
|View full text |Cite
|
Sign up to set email alerts
|

Increased Histone H3 Phosphorylation in Neurons in Specific Brain Structures after Induction of Status Epilepticus in Mice

Abstract: Status epilepticus (SE) induces pathological and morphological changes in the brain. Recently, it has become clear that excessive neuronal excitation, stress and drug abuse induce chromatin remodeling in neurons, thereby altering gene expression. Chromatin remodeling is a key mechanism of epigenetic gene regulation. Histone H3 phosphorylation is frequently used as a marker of chromatin remodeling and is closely related to the upregulation of mRNA transcription. In the present study, we analyzed H3 phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Recent reports have clearly demonstrated significant differences in epigenetic modification patterns between neuronal and non-neuronal cells (Bousiges et al, 2013;Matt et al, 2016;Mori et al, 2013).…”
Section: Cell-specific Lps-induced Increase In Histone H3 Phospho(s10...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have clearly demonstrated significant differences in epigenetic modification patterns between neuronal and non-neuronal cells (Bousiges et al, 2013;Matt et al, 2016;Mori et al, 2013).…”
Section: Cell-specific Lps-induced Increase In Histone H3 Phospho(s10...mentioning
confidence: 99%
“…Phospho(S10)-acetylation(K14) of histone H3 (H3S10phK14ac) is dynamic and reversible and could serve to amplify the readout of upstream signaling pathways causing greater changes in the overall charge density of tails that resulting in greater modification of the chromatin structure of target genes (Colvis et al, 2005;Nowak and Corces, 2000;Rea et al, 2000;Thompson et al, 2001). Further evidence showed an increase of H3 phosphorylation in hippocampal neurons after seizures, that occurs in the c-Fos promoter region determining an elevation of c-Fos gene expression (Clayton et al, 2000;Mori et al, 2013). c-Fos is one of the most widely studied target genes because it is critical for synaptic plasticity and hippocampal memory Fleischmann et al, 2003;He et al, 2002;Tischmeyer and Grimm, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…2 c) [74] . Similarly, long-term mental and pain stress on the neurons of the sensory motor cortex and midbrain reticular formation in rats with high excitability threshold found to exhibit higher basal level of H3Ser10 histone phosphorylation in the midbrain reticular formation neurons than rats with low excitability threshold [75] . There is a need for some more studies of histone phosphorylation, to establish its clear role in neurological implications.…”
Section: Histone Phosphorylation: Neurological Implicationsmentioning
confidence: 84%
“…Phosphorylated histone-H3 has the property of a lower binding capacity to the associated DNA due to a double-negative charge and is a prerequisite for transcription. The BrdU analysis in combination with the pHH3 detection is therefore very specific concerning the mitotic detection of a silent neural stem cell potential [ 47 ]. The analysis showed that the significantly largest proportion of pHH3 + cells was detected in the area of the PVCN ( Figure 8(b) ).…”
Section: Discussionmentioning
confidence: 99%